An Analysis Method for Time-, Frequency-, and Energy-Domain Characteristics of Downhole Microseismic Signals and Its Application - Xiao-xu Gao; Xiang-xu Pan; Guang-an Zhu (Shock and Vibration)
Based on SOS microseismic (MS) monitoring system of a certain mine, time-, frequency-, and energy-domain characteristics of MS signals are analyzed by comprehensively applying one-dimensional discrete Fourier transform (DFT) and one-dimensional discrete wavelet transform (DWT). The technology is employed to explore MS signals from incident and transmitted waves on the fault plane. The research results show that, within the time domain, the transmitted waves are found to have the rapidly reducing velocity and a few wave crests; within the frequency domain, the fault plane presents a low-pass filtering effect on incident waves; within the energy domain, the fault generally shows the vibration-attenuating effect on MS signals. The analysis method is used for the No. 3307 working face of a certain mine to realize the prediction on a buried fault in the middle part of the working face, and it is validated to have a favorable effect.